Academic research writing: how novice researchers could be pedagogically supported? - Musah, Mohammed Borhandden (2015)
Academic research writing (ARW) necessitates the independent search for appropriate information, its critical evaluation and its presentation. It is at the pinnacle of student learning and student development in the disciplinary scholarship. Graduate students need to be able to think and act as researchers while conducting the research and while writing it out. Moreover, ARW is social-situated, and bound with the conventions of the discursive disciplinary community. In the process of writing, NRs are in the process of meaning-construction, “whereby the author’s discursive identity is forged and made visible to the readers” [1: 444]. Various research studies have proved a four-factor structure of ARW, i.e.: General writing skills, Discursive writing skills, Technical writing skills, Writing in English. Novice researchers (NRs) entering the higher education institutions (HEIs), hence, must be meticulously prepared on all these four dimensions. Based on a structured review of related literature, this paper first discloses these four dimensions and secondly explores the pedagogical implications of these dimensions. The findings of the study are very significant as it would help HEIs with insights on how to provide for additional, but appropriate pedagogical support for the NRs.